Training material for producing national human development reports : the Human Development Index (HDI) - Oxford Poverty & Human Development Initiative (OPHI) (Oxford Poverty & Human Development Initiative (OPHI), 2011)
This paper discusses the construction and analysis of the Human Development Index (HDI). Since 1990 the HDI has had three dimensions: a long and healthy life, knowledge, and a decent standard of living. The indicators used to inform each dimension have, however, changed over time—most recently in the 2010 HDR. The latest method along with changes over time are all explained here.